A Regra, norma e modelo da escravidão no Brasil colonial pela visão do jesuíta Jorge Benci (1681-1707) - Celestino, Marina Angélica (2021)
The present work deals with the work Christian Economy of the Lords in the Government of the Slave (1705) composed of four sermons preached by the member of the Society of Jesus, Jorge Benci, in the 17th century. The research works on post-Tridentine concepts about the dogmas of the Catholic faith, the processes that imply indoctrination, discursive practice and its due relevance to the degree of scholarship required by the Jesuits. The Christian precepts in the 17h century govern the way of thinking and determining the social and economic relations of Bahia's sugar elite, as well as legitimizing the transatlantic traffic so that the lords of Brazil and the Church can use the slave business, with Benci's work as the main source. to verify his perspective on slavery in Brazil